Reprodutibilidade do teste do degrau incremental em pacientes com doença pulmonar obstrutiva crônica - Cianci, Reinaldo Giovanini (2009)
The determination of the functional capacity has been considered an important part of assessment in patients with chronic obstructive pulmonary disease (COPD), especially by using testes which are representatives of daily activities. Besides these characteristics the step test is considered a portable test and requires low costs. The objective of this study was to test the reproducibility of an incremental step test (IST), and secondarily to correlate its performance, i.e., number of steps to metabolic, ventilatory, cardiovascular, and perception of effort variables. Twenty-one patients with COPD (FEV1: 47.6  13.2% of predict) underwent two IST (IST-1 and IST-2) on different days (2 or five days apart), after spirometry post-bronchodilation (400 g salbutamol). IST was performed on a 20-cm high, single step, paced externally by na auditive signal (initial cadence of 10 steps/min with increments o one step each 30s, until limit of tolerance). IST-1 and IST-2 were highly reproducible with no significant difference between variables at peak of exercise: peak oxygen consumption (1.24  0.42 vs 1.26  0.42 L/min), minute ventilation (42,8  14,8 vs 40,9  13,5 L/min), heart rate (138.4  21.2 vs 133.9  19.9 bpm), peripheral oxygen saturation (88.0  4.7 vs 88.0  4.0%), and number of steps (111.3  59.5 vs 113.4  61.4), respectively. Significant correlations were observed between number of steps and pulmonary function (FEV1: 0.65; FVC: 0.60 and SpO2 at rest: 0.65) and with variables at peak of exercise (VO2: 0.78; VE: 0.69 and HR: 0.61). IST is a reproducible test and its best performance is related to better pulmonary function and to the highest metabolic and cardiorrespiratory responses at peak of exercise.